Impact of energy reform in fertilizer market in Mexico - G. Vargas-Hernández, José (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
Energy reform will bring about major changes in the economy of Mexico, mainly due to the introduction of domestic and foreign-in the exploitation and marketing of petrochemical products-both private initiative. The fertilizer sector is undoubtedly one of the most affected by this approval. The measures agreed within this reform will directly impact domestic production, the quantity of imports and, above all, the demand for these products. The aim of this paper is to analyze the current and future situation of the sector, in order to study the economic impact of this reform and alternatives concerning the present situation live existing and emerging companies in this market.
Keywords: Fertilizers; Mexico; Energy reform